2005
DOI: 10.1007/s10681-005-0816-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of large-seeded common bean cultivars under sustainable cropping systems in Spain

Abstract: Approaches are needed to broaden the genetic base and improve earliness and yield potential of large-seeded beans under sustainable cropping systems. The objective of this research was to develop adapted dwarf bean populations having a commercial seed quality and yield suitable for the production in the South of Europe. The original base populations were produced from crosses between genotypes within each Mesoamerica, Nueva Granada and Peru races, and between Peru and Nueva Granada, and Mesoamerica and Nueva G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…The relatively high proportion of breeding lines susceptible to BCMV in this study is in accordance with previous reports by Sáiz et al (1995) and Santalla et al (2004). A top necrotic reaction to the BCMNV strain NL-3K indicated the presence of the I resistance allele for BCMV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relatively high proportion of breeding lines susceptible to BCMV in this study is in accordance with previous reports by Sáiz et al (1995) and Santalla et al (2004). A top necrotic reaction to the BCMNV strain NL-3K indicated the presence of the I resistance allele for BCMV.…”
Section: Discussionsupporting
confidence: 92%
“…The relatively high proportion of breeding lines susceptible to BCMV in this study is in accordance with previous reports by Sáiz et al (1995) and Santalla et al (2004) A top necrotic reaction to the BCMNV strain NL‐3K indicated the presence of the I resistance allele for BCMV. Seven breeding lines (0028‐02, 0219‐06, 0323‐01, 0323‐13, 0323‐15, 0323‐17, and 0452‐03) were symptomless to both virus strains, and were thus expected to carry recessive resistance alleles at one or more bc loci (Drijfhot, 1978) because these lines did not show necrosis.…”
Section: Discussionsupporting
confidence: 92%
“…A few studies have explored genotype improvement in the pre-breeding phase and the earliest stages of cultivar development [25,26,30]. Others reported on research initiated at the F4 and F5 generations, after a number of traits have been stabilized [23,31]. Finally, selections within intercrops have been made at the end of the breeding process with cultivars ready for release [32,33].…”
Section: Open Accessmentioning
confidence: 99%
“…Trait-based competitive ability (31) 'There are varieties that have many leaves which can affect the maize, the ones that don't have many leaves are better in the intercrop' 'Imvange produces pods at different places, some at the bottom, some in the middle, some at the top. Imvange also doesn't make competition to the maize in terms of making it fall down because the stems aren't big' 'Ngwinurare doesn't make competition to the maize and the maize doesn't compete with the beans. '…”
Section: Comparisonsmentioning
confidence: 99%
“…Gil and De Ron (1992), Rodiño et al (2001b) and Santalla et al (2002) have characterized the common bean germplasm from the Iberian Peninsula (Spain and Portugal) for morphological and agronomic traits and molecular profi le. Few reports are available on the reaction of these germplasm to the main diseases (Ferreira et al, 2003, Santalla et al, 2005. Availability of disease resistant high yielding cultivars could reduce pesticide usage and facilitate sustainable bean production.…”
mentioning
confidence: 99%